Factors associated with menstrual dysfunction and self-reported bone stress injuries in female runners in the ultra- and half-marathons of the Two Oceans. Issue 10 (11th May 2007) - Micklesfield, L K; Hugo, J; Johnson, C; Noakes, T D; Lambert, E V
Abstract : Objective: To investigate factors associated with menstrual dysfunction, self-reported bone stress injuries and energy balance in women runners. Methods: 613 runners were randomly sampled during the registration period for an endurance event. Demographic information, including self-reported height and weight, training and injury history and menstrual history, was collected by questionnaire. Results: Ultra-marathon (ULTRA) participants (n = 276) were significantly older (mean (SD) 39 (8.2) vs 34 (10.5) years; p<0.001), lighter (58.2 (6.6) vs 59.6 (8.3) kg; p<0.05) and reported a higher training volume (p<0.001) than half-marathon (HALF) participants (n = 337). Significantly more ULTRA subjects than HALF subjects reported a previous bone stress injury (21% vs 14%; p<0.05). There was no difference between the groups for menstrual status, but age at menarche was later (p<0.01) in the ULTRA group. Data were combined according to the absence (REG; n = 368/602 (61%)) or presence (IRREG; n = 234/602 (39%)) of a history of menstrual irregularity. Subject morphology was similar between groups, but the IRREG group had a higher self-reported measure on the self-loathing subscale (SLSS; p<0.01). The whole group was then classified according to current menstrual status, with 165 women being classified as currently irregular. (OLIGO/AMEN; 11.6%) and 445 women as currently regular (EUMEN; 88.4%). There were no morphological differences between the groups, however the OLIGO/AMEN group had a later age of menarche (p<0.01) than the EUMEN group. Further, women who reported a previous bone stress injury had higher SLSS scores than those who did not (2.91 (0.98) vs 2.68 (0.84); p<0.05). Conclusions: There may be two independent mechanisms associated with energy balance, which are related to bone stress injuries, but may not necessarily be related to menstrual dysfunction.